Peranan Lingkungan terhadap Semangat Belajar dalam Khazanah Kitab Kuning - Muhammad Barmawi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Based on scientific treasure, motivation has an important role in encouraging students to reach their goals. Because of its importance in education, the writer wants to conduct a research about the concept of motivation in the treasure of classic books (kitab kuning) especially in al-Zarnuji’s book entitled Ta’lim alMuta’allim which describes about education in Islamic perspective. The research uses descriptive analysis method which describes and analyzes the content of the book. The analysis result brings to three conclusions. First, motivation is divided into two parts they are intrinsic and extrinsic motivation. Second, environment, especially family environment, has a big role in motivating students to learn. Finally, the theory of motivation mentioned in Ta’lim al-Muta’allim discusses about extrinsic motivation only, while intrinsic motivation is the realization of extrinsic motivation.